Seed-borne infestation and management of Alternaria Species in mustard seed at Chitwan district, Nepal - Rijal, Prashant; Subedi, Subash; Adhikari, Chiran; Shrestha, Sundarman; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2020)
Alternaria blight in mustard cause heavy damage to the foliar parts resulting into poor growth and development of plants and thereby reduces seed yield. Inorder to manage Alternaria infestation in mustard seed for yield maximization, an experiment was conducted in the plant protection laboratory in Nepal Polytechnic Institute, Bharatpur, Chitwan in 2018, using Completely Randomized Design (CRD) with four replicates. Five treatments i.e.Uthane M-45 (2g/kg), Neem powder (3 g/kg), Bojho powder (4g/kg), Trichoderma harzianum, (107 Conidia/mL) and control (without treatment) were used for seed treatment of local variety of Mustard. Four hundred seeds for each treatment (25 seeds in each petriplate) were plated using triple layers of moistened blotter paper in petriplate and incubated at (27±20C) for 2 days and followed deep freezing for 24 hrs. Data of disease incidence and seed germination were recorded in 3, 7 and 10 days after incubation (DAI). Seedling vigor and seedling weight were also recorded at 5 DAI. The percentage of Alternaria spp incidence on seeds at different DAI showed highly significant with respect to different treatments. Application of Uthane M-45 and T. harzianum significantly reduced the seed-borne infection of Alternaria spp. as compared to control. At 3 DAI Uthane M-45 completely checked the pathogen however, only 4% and 5% disease incidence was observed in 7 DAI and 10 DAI respectively. Bio control agent Trichoderma harzianum was found next best alternative after Uthane M-45 to control disease. Plant extract Bojho powder and Neem powder were found better than control to check the disease. Furthermore, highest germination (76%) was observed in Trichoderma treatment whereas, lowest germination was found in control.